Harmony Then Divorced: The Dynamics of the Relationship between the Student Movement and the New Order in 1966-1980 - Haidar Trisna Tanaya (Universitas Negeri Semarang, 2026)
The Student Movement has a long history since back to colonial times. The Student Movement is formed from students who have thoughts of change which then form a movement to make corrections, criticisms and changes in the social, political and government fields. The Student Movement during the New Order was seen as being in a depressed position, but on the other hand, in fact the Student Movement had a good relationship with the New Order at the beginning of the New Order. The Student Movement can be said to have contributed to the birth of the New Order through demonstrations, one of which was the Tritura action in 1966. The formation of a harmonious relationship between the Student Movement which was known to be critical and the militaristic New Order did not happen suddenly, but there were several factors that contributed to it. behind it. This study tries to analyze and reveal the factors that caused the Student Movement to have a harmonious relationship with the New Order while at the same time revealing the causes of the harmonious relationship rift that caused the Students and their Movement to experience extraordinary repression and intervention from the New Order